Financial Valuation of Fortum Corp - Serhan, Rami; Ali, Tanweer; Sieber, Patrik, 1977-; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2024)
Abstract: This thesis presents a financial valuation of Fortum Corp, a key player in the energy sector. Utilizing methods like Discounted Cash Flow (DCF) and peer analysis, it aims to ascertain Fortum's intrinsic value, considering its diverse energy production and substantial market presence. With over a 150 power plants in total, and operating profit of 1 662 million EUR. Fortum's financial statements and market performance are critically analysed. The study also examines the impact of Fortum's research and development in renewable energy and decarbonization efforts. This concise assessment of Fortum's financial stability and future prospects contributes to the broader understanding of valuation in the energy sector, highlighting investment opportunities and challenges in this vital industry.
Vedoucí práce: Tanweer Ali
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: bachelor of business administration [obor bakal. práce]; bakalářské práce; bachelor's theses